2023
DOI: 10.1186/s40001-023-00991-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of telemonitoring combined with intensive patient support with standard care in patients with chronic cardiovascular disease - a randomized clinical trial

Abstract: Importance Healthcare concepts for chronic diseases based on tele-monitoring have become increasingly important during COVID-19 pandemic. Objective To study the effectiveness of a novel integrated care concept (NICC) that combines tele-monitoring with the support of a call centre in addition to guideline therapy for patients with atrial fibrillation, heart failure, or treatment-resistant hypertension. Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The two composite endpoints as well as many secondary endpoints, such a mortality showed an advantage for NICC when compared with SoC. 7 However, the trial neither showed a significant difference in the number of hospitalisation days nor a significant difference in the number of hospitalisations between the two treatment groups. For patients in the NICC group, the treating physicians recommended, however, a visit to an established doctor or even a hospital in case patients had unusual telemonitoring findings or called the care centre.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The two composite endpoints as well as many secondary endpoints, such a mortality showed an advantage for NICC when compared with SoC. 7 However, the trial neither showed a significant difference in the number of hospitalisation days nor a significant difference in the number of hospitalisations between the two treatment groups. For patients in the NICC group, the treating physicians recommended, however, a visit to an established doctor or even a hospital in case patients had unusual telemonitoring findings or called the care centre.…”
Section: Discussionmentioning
confidence: 93%
“…11 The number of inpatient days in hospital were approximately 1.5 lower in the NICC group (CI 0.96 to 1.81). 7 Therefore, direct cost was expected to be lower in the NICC group compared with the SoC group. Indeed, direct cost was approximately €322.55 lower in the NICC group compared with the SoC group during the 1 year treatment period (CI €156.56 to €488.53; table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed assessments were at 6 months and 1 year after randomization. The CONSORT flowchart has been provided in (7). The primary diagnosis was AF, HF, and TRH in 265 (27.7%), 406 (42.4%), and 286 (29.9%) patients, respectively.…”
Section: Patientsmentioning
confidence: 99%
“…In addition to improving individual health outcomes, effective prevention and management of CVDs can also have broader societal benefits. By reducing the burden of CVDs, healthcare systems can allocate resources more efficiently and effectively, and the economic burden of CVDs can be reduced, leading to increased productivity and economic growth [7]. Recent years have seen significant advances in the prevention and management of CVDs.…”
Section: Introductionmentioning
confidence: 99%